Effect of Pyrethroid on Fertility of Adult Rats - Nasr, Sawsan A.; Moghazy, Asmaa M.; Osman, Amany; Nasr, Nadia (European Journal of Applied Sciences, 2021)
Sixty Adult female albino rats were randomly divided into seven groups as fellow group (1) normal control, Inductive group (1) in this group animals received low dose 12 mg/kg) from permethrin, Inductive group (2),in this group animals received high dose ( 75mg/kg.) from permethrin, group 4: treated group, animals received Vit E. (500 mg/ mg/Kg.) and then received low dose of permethrin (12 mg/k.) after half hour, group 5: treated group, animals received Vit E. (500 mg/ mg/Kg.) and then received high dose of permethrin (75 mg/k.) after half hour,Group 6: treated group, animals received Vit E. (250 mg/ mg/Kg) and then received low dose of permethrin (12 mg/k. ) after half hour and group 7: treated group, animals received Vit E. (250 mg/ mg/Kg.) and then received low dose of permethrin (75 mg/k. ) after half every doses received daily. At the end of the experimental period Blood samples were withdrawn,we determine triglyceride (TG), total cholesterol (TC), blood urea and creatinine. Also Estradiol and progesterone, total T3 , T4 and TSH levels in plasma of female were measured. The excised ovary in each group used to measure MDA, as a marker for lipid peroxidation (LPO) and GSH content in ovary tissue . In the same time the ovarian tissue which were removed after sacrifice, it was used for histological examination for the evaluation and assessment of the d fibrous formation, in injuries tissue. permethrin with different doses (12 and 75 mg/kg respectively) significantly (p≤ 0.05) increased the MDA and significantly decreased (p< 0.05) in GSH content in ovary tissue versus control animal. Though treatment with vitamin E after permethrin with different dose (250 and 500 mg/kg respectively) significantly deceased the MDA content versus permethrin group (12 and 75 mg/kg respectively) and Vit E treatment increased GSH content in a group treated with (permethrin 75 mg/kg b.w). The level of both serum estrogen (E2) and progesterone were significantly (p<0.05) decreased in a permethrin group in both doses (12 and 75 mg/kg ) when compared to control group. While, treatment with Vit E ameliorate the level of E2 and progesterone. Treating rats with permethrin led to a significant decrease in triiodothyronine (T3) and thyroxine (T4) as well as a significant increase of thyroid-stimulating hormone (TSH) when compared to control group. Administration of Vitamin E and permethrin caused an improvement in the levels ofT3 and T4 and TSH. This study was designed to elucidate premethrin effects at doses (12and75mgb) for 30 days, causing reproductive toxicity through several biotransformation metabolites processes. Focusing on ovarian injures and reproductive efficacy. treated ovarian tissue showed histological alterations represented by reduction number of different follicles, with absent mature follicles in high dose premethrin, or follicles without oocytes and zone granulose residual with vacuolar change finally necrotic areas. Special stain for connective tissue fibersMasson’s trichrome, showed accumulation of fibrous proportional to the dose. while the Immuno- reactive of TNF-ᾳ assayment many necrotic area evidence of premethrin toxicity, also its dwindling effect on proliferating cell nuclear antigen (PCNA)which affected the efficiency of DNA, and consequently on the cell proliferative activity. In contrast, evaluate the effective therapeutic role of Vitamin E at doses (250 and 500 mg bw),as an antioxidant clarified, which is explained by the histological in the results. This study reveals that chronic exposure to premerthin even low dose alters ovarian cycle activity . Hence, Premethrin exposure threat fertility of humans and animals.it is speculate that the positive effect of the Vitamin E by its antioxidant activity able to protect ovarian tissues the premerthin toxicicity